Environmental diplomacy : an effective tool for small island states to define a more dynamic role in international environmental-development negotiations. - Griffith, Mark (1992)
Argues that for small island states to continue to use environmental diplomacy to influence international environment-development negotiations, they must identify areas of common conern.